Aggression Toward Healthcare Workers: The Effect of Indirect Victimization on Burnout Dimension. Issue 8 (14th September 2021) - Ferretti, Fabio; Gualtieri, Giacomo; Carabellese, Fulvio; Gusinu, Roberto; Masti, Alessandra; Pozza, Andrea; Coluccia, Anna
ABSTRACT: Physical and verbal aggression can occur with significant frequency in the working life of healthcare workers. The effects of such events on the psychological health of victims of workplace aggression have been shown, but their indirect effect has not yet been studied. The present brief report describes an exploratory study investigating the effect of indirect victimization on burnout dimensions in healthcare workers. Two hundred ninety-seven workers completed an online questionnaire to detect direct/indirect workplace-related victimization experiences and the Maslach Burnout Inventory (MBI). The direct physical victimization typology produced a significant effect on all the burnout dimensions while the verbal type had a significant impact on emotional exhaustion and depersonalization, but not on personal accomplishment. Indirect victimization due to verbal aggression produced a significant effect on depersonalization. Aggression prevention and risk containment is important to safeguard workers against violent events but also to preserve perception of a safe workplace protected from all types of aggression.